2013
DOI: 10.1093/deafed/ent025
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Experiences of Receiving and Living With Sequential Cochlear Implants: An Interpretative Phenomenological Analysis

Abstract: There is currently a unique opportunity to examine the experiences of young people who receive a second sequential cochlear implant (SCI), after only having had 1 cochlear implant (CI) for most of their lives. Eleven young people who had opted to receive an SCI were interviewed. Interpretative phenomenological analysis resulted in the identification of 6 master themes. Most participants enjoyed improved confidence and social well-being following their SCI and felt that 2 CIs were superior to 1. The majority id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 34 publications
3
37
0
8
Order By: Relevance
“…Accordingly, a variety of studies has found deaf youth to report greater self-confidence and social well-being after receiving CIs (e.g., Dammeyer, 2010;Hilton, Jones, Harmon, & Cropper, 2013;Jambor & Elliott, 2005;Leigh, Maxwell-McCaw, Bat-Chava, & Christiansen, 2009;Wheeler, Archbold, Gregory & Skipp, 2007). As Archbold (2015) and others have indicated, however, the situation is complicated.…”
Section: Social Maturity Among Deaf Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a variety of studies has found deaf youth to report greater self-confidence and social well-being after receiving CIs (e.g., Dammeyer, 2010;Hilton, Jones, Harmon, & Cropper, 2013;Jambor & Elliott, 2005;Leigh, Maxwell-McCaw, Bat-Chava, & Christiansen, 2009;Wheeler, Archbold, Gregory & Skipp, 2007). As Archbold (2015) and others have indicated, however, the situation is complicated.…”
Section: Social Maturity Among Deaf Learnersmentioning
confidence: 99%
“…As Archbold (2015) and others have indicated, however, the situation is complicated. This is especially true among older students and young adults for whom the language demands are greater and the contexts of language and social interaction associated with social maturity are more abstract and complex (Dammeyer, 2010;Hilton et al, 2013). Knutson, Boyd, Reid, Mayne, and Fetrow (1997), Bat-Chava and Deignan (2001), Jambor and Elliott (2005), and Wheeler et al (2007) thus found that although deaf youth reported improved communication with hearing peers after receiving CIs, relatively few children, those with the best speech and hearing, were fully accepted by hearing peers.…”
Section: Social Maturity Among Deaf Learnersmentioning
confidence: 99%
“…Wheeler et al (2007), Mather et al (2011) and Hilton et al (2013) conducted individual interviews with small numbers of teenagers. The research highlighted that the teenagers generally felt positive towards their cochlear implant as a result of improvements in their listening and communication abilities, although adapting to a cochlear implant, particularly if it is the second device, can be a long and difficult process.…”
Section: List Of Figuresmentioning
confidence: 99%
“…Interviews with the teenagers revealed that whilst they benefited from increased confidence and an improved social life, they also experienced challenges adapting to the sound of the second device. They reported both hearing and deaf identities but also a feeling of difference, despite being more integrated into the hearing world (Hilton et al, 2013). Rehabilitation following surgery may not be straightforward for teenagers as it requires patience and commitment, the extent of which may not be fully appreciated beforehand (Mather et al, 2011).…”
Section: Bilateral and Sequential Cochlear Implantsmentioning
confidence: 99%
See 1 more Smart Citation